Reproductive Seasonality of Coral Assemblages in the Karimunjawa Archipelago, Indonesia - Wijayanti, Diah P.; Indrayanti, Elis; Wirasatriya, Anindya; Haryanto, Arfiyan; Haryanti, Dwi; Sembiring, Andrianus; Fajrianzah, Tyas A.; Bhagooli, Ranjeet (Frontiers in Marine Science, 2019)
Equatorial corals were previously thought not to spawn synchronously at the assemblage level. However, recent studies have reported multi-specific coral spawning events in equatorial regions. Here, we report the reproductive activity of 21 Acropora species in the Karimunjawa Archipelago over five consecutive years (2008–2012). We also infer the month of spawning for Acropora humilis, Acropora gomezi, and Acropora muricata from the presence of mature oocytes. We found that Acropora assemblages exhibit a high degree of inter-specific reproductive seasonality. The highest proportion of colonies with mature oocytes was observed in March 2011 (65%, n = 80). Oocytes likely developed during June–March, 6 to 10 months before spermatogenesis. Spermatocytes were observed in samples collected during March; however, the onset of spermatogenesis could not be precisely determined as samples were not collected in January and February. This was because of weather constraints and difficulty in detecting the early stages of spermatogenesis. Multi-specific spawning events were observed during the first transition period (March–April) and the second transition period (September–October) between monsoons. The number of species containing mature oocytes was higher during March–April (12 species) and September–October (8 species). Spawning patterns likely follow the lunar cycle. However, two distinct spawning events coincided with two periods of higher temperature (March–April and September–October). Daily temperature records indicate that spawning occurred on days where temperature dropped before the expected spawning time during the warming period. During the period of rising temperature, wind speeds were lower, which might serve as a signal leading to the multi-specific spawning of corals in the tropics, at least in the Karimunjawa Archipelago of Indonesia.